2005
DOI: 10.1177/0095798405281025
|View full text |Cite
|
Sign up to set email alerts
|

Africentric Cultural Values, Psychological Help-Seeking Attitudes, and Self-Concealment in African American College Students

Abstract: This study investigated the relationships among Africentric cultural values (i.e., the extent to which an individual adheres to a worldview emphasizing communalism, unity, harmony, spirituality, and authenticity), favorable psychological help-seeking attitudes, perceived counseling stigma, and selfconcealment (i.e., the tendency to withhold personal, sensitive information that is perceived as negative or upsetting) in a sample of African American college students. The authors found that for both African Americ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(84 citation statements)
references
References 35 publications
3
78
1
2
Order By: Relevance
“…Conceptually, while considered an adaptive behavioral tendency in some sociocultural contexts (O'Neil, Helms, Gable, David, & Wrightsman, 1986;Wallace & Constantine, 2005), self-concealment may serve as a maladaptive control-and avoidance-focused emotion/behavior regulation strategy in other contexts (Masuda, Anderson, et al, 2011;Masuda, Boone, & Timko, 2011). Research has shown that self-concealment is positively associated with global psychological symptoms (Cramer, 1999), depression (DiBartolo, Li, & Frost, 2008), anxiety (Larson & Chastain, 1990;Potoczniak, Aldea, & DeBlaere, 2007), and various forms of somatic complaints (Larson & Chastain, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Conceptually, while considered an adaptive behavioral tendency in some sociocultural contexts (O'Neil, Helms, Gable, David, & Wrightsman, 1986;Wallace & Constantine, 2005), self-concealment may serve as a maladaptive control-and avoidance-focused emotion/behavior regulation strategy in other contexts (Masuda, Anderson, et al, 2011;Masuda, Boone, & Timko, 2011). Research has shown that self-concealment is positively associated with global psychological symptoms (Cramer, 1999), depression (DiBartolo, Li, & Frost, 2008), anxiety (Larson & Chastain, 1990;Potoczniak, Aldea, & DeBlaere, 2007), and various forms of somatic complaints (Larson & Chastain, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…(Jessie, Uni. 1) According to Irungu (2013), African students have a cultural bias against seeking counseling (see also Wallace & Constantine, 2005). This was echoed by the attitudes of the students in our study:…”
Section: What Strategies Do Students Use To Cope With the Challenges mentioning
confidence: 54%
“…According to most African cultures, the relative who has more is expected to share with others in the family-an expectation that can create incredible pressures. (Irungu, 2013, p. 174) This collectivism is often stated to be a common feature of many African societies (Hofstede, 2001;Hyams-Ssekasi, 2012;Irungu, 2013;Wallace & Constantine, 2005) and not only implies an obligation to share finances but also provides a key support mechanism for individuals. A number of studies have found that African students struggle with the differences in cultures between the individualism found in the United Kingdom and the United States, and their own more communal cultures (Boafo-Arthur, 2014;Fischer, 2011;Irungu, 2013;Mwara, 2008).…”
Section: Challenges Faced By Black-african International Studentsmentioning
confidence: 99%
“…An, admittedly speculative, explanation is that as high self-concealers have smaller social networks and prefer to stay relatively aloof from others (CepedaBenito & Short, 1998;Wallace & Constantine, 2005), they may therefore less frequently deploy sexual activities one would likely keep secret (other than those generally accepted and regarded as a matter of privacy such as masturbation). Hence, it may be that the more one is a self-concealer, the less sexual activities one has to keep secret.…”
Section: Discussionmentioning
confidence: 99%